Feed the future-usaid kenya accelerated value chain. Development program. Potato value chain. Six-year final report - International Potato Center (International Potato Center, 2021)
Potato plays an important role in Kenya’s food and nutrition security plan - part of the Big Four Economic Development Strategy. The crop is cultivated by approximately 800,000 smallholder farmers and a few medium and large-scale farmers. The sector employs another 2.5 million people - transporters, distributors, processors, vendors, retailers, and exporters - who derive their livelihoods along the value chain. Production has fluctuated over the last decade, despite a steady increase in area from 122,542 to 212,976 ha from 2010 to 2019, with productivity steadily declining from 22 t/ha in 2010 to less than 10 t/ha in 2019, representing a loss of 2.7 million tonnes of food, or an additional 100,000 ha needed to meet the same production as 2010. The opportunities for unit-area yield gains in potato outcompete other crops, making potato a strong option for addressing food, economic and nutrition security in Kenya. To address losses in productivity and fragmented value chains, Accelerated Value Chain Development (AVCD) supported the development of a private sector-led value chain, integrating county governments in leading/supporting interventions to disseminate productivity-enhancing technologies, strengthen seed systems and develop farmer producer organizations (FPOs) to improve equality and opportunity in the value chain. In AVCD phase 1 (2015–2018), the potato value chain (PVC) covered the counties of Elgeyo-Marakwet (EMC), Meru, Nandi, and Uasin Gishu (UGC), while Phase 2 (2019– 2021) was in Bungoma and Taita Taveta. The depth and breadth of the AVCD potato component reached and benefited thousands of smallholder farmers. Over six years, 74,690 smallholder farmers were reached with AVCD agricultural and nutrition-related interventions, of whom 72,260 applied productivity-enhancing technologies following season-long practical training on learning farms hosted by farmer groups and led by government extension workers. As a result of increasing production and productivity, farmers collectively generated 33,977,789 USD in value of sales from potato: 27.6M USD in phase 1 and 6.3M USD in phase 2. This represents an increase in the value of sales generated per farmer per hectare of 1,348 to 2,367 USD and 481 to 1,322 USD in phases 1 and 2, respectively. This further represents project-direct return on investment of 1 to 9.79 USD on the 3.47M USD USAID investment in the potato value chain. The return is expected to be notably higher when taking into account the value of sales generated in phase 1 counties since the project ended there in 2018. This increase in value of sales was also accompanied by increases in gross margin in phase 1 from a baseline 721 USD/ha to 1,680 USD/ha, demonstrating that the increase was not solely due to increases in production costs but also to increases in farmer profits. In phase 2 (exclusive of the extension component) farmer yields increased by 49% from 7.7 to 11.5 t/ha which, over a final area of 6,096 ha of 17,779 smallholder farmers, represented an additional 23,165 tonnes of food produced over two cropping seasons compared to baseline yields, and which contributed to greater sales of potato. Table I summarizes the main achievements of the potato component of AVCD.